2014
DOI: 10.1017/s0033291714001147
|View full text |Cite
|
Sign up to set email alerts
|

Adapted cognitive–behavioural therapy required for targeting negative symptoms in schizophrenia: meta-analysis and meta-regression

Abstract: The co-occurring beneficial effect of conventional CBT on negative symptoms found in older studies was not supported by more recent studies. It is now necessary to further disentangle effective treatment ingredients of older studies in order to guide the development of future CBT interventions aimed at negative symptom reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(80 citation statements)
references
References 59 publications
4
72
2
2
Order By: Relevance
“…Some earlier studies reported significant benefits for negative symptoms at the end of treatment and/or at post-treatment follow-up (Wykes et al 2008;Klingberg et al 2011;Grant et al 2012). However, a more recent meta-analytic review indicated that the overall effects were small and nonsignificant, suggesting that CBT studies focused on psychotic symptoms may not reduce negative symptom as well as previously thought (Velthorst et al 2015). Importantly, neither SST, CET, nor CBT directly address any of the four processes hypothesized to contribute to motivational negative symptoms.…”
Section: Conventional Approachesmentioning
confidence: 90%
“…Some earlier studies reported significant benefits for negative symptoms at the end of treatment and/or at post-treatment follow-up (Wykes et al 2008;Klingberg et al 2011;Grant et al 2012). However, a more recent meta-analytic review indicated that the overall effects were small and nonsignificant, suggesting that CBT studies focused on psychotic symptoms may not reduce negative symptom as well as previously thought (Velthorst et al 2015). Importantly, neither SST, CET, nor CBT directly address any of the four processes hypothesized to contribute to motivational negative symptoms.…”
Section: Conventional Approachesmentioning
confidence: 90%
“…Hierbei ergaben sich jeweils Behandlungseffekte im mittleren Effektstärkenbereich, was in etwa den positiven Effekten der KVT für Positivsymptomatik bei Schizophrenie entspricht [Wykes et al, 2008]. Gleichzeitig berichteten 2 Meta-Analysen jedoch, dass gerade neuere und qualitativ hochwertige Studien keine signifikanten Behandlungseffekte für die Negativsymptomatik mehr zu finden scheinen [Velthorst et al, 2015;Wykes et al, 2008].…”
Section: Definition Der Negativsymptomatik Bei Schizophrenieunclassified
“…However, a recent meta-analysis found no treatment effects of CBT on negative symptoms, although positive effects have been reported regarding global functioning (d = 0.378) and mood (d = 0.363). 53 Interestingly, individualized protocols and older trials seem to be associated with negative symptom improvement.…”
Section: ■ Results and Discussionmentioning
confidence: 99%